2009
DOI: 10.1111/j.1651-2227.2008.01084.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of passive smoking and breast feeding on serum antioxidant vitamin (A, C, E) levels in infants

Abstract: Tobacco smoke exposure of infants significantly decreases their serum antioxidant vitamin A, C and E levels. However, breast feeding may help to prevent the decrement of antioxidant vitamin levels of passive smoking infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 24 publications
(40 reference statements)
0
11
0
2
Order By: Relevance
“…Comparison of values for duration and pattern of active exposure showed a high concordance with 86% of mothers reporting 1 periconceptional month of exposure corresponding to reported smoking in B1 only and 98% of mothers who reported 2 or 3 periconceptional months of exposure corresponding to reported smoking in B1–M1 and B1–M2, respectively. Given potentially harmful effects of passive smoke exposure (Hozyasz and Chelchowska,2004; Yilmaz et al,2009), the highest reported duration for passive and/or active smoke exposure was used. For example, if the mother reported 4 months of passive smoke exposure and 3 months of active smoking, the highest reported duration would be 4 months.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparison of values for duration and pattern of active exposure showed a high concordance with 86% of mothers reporting 1 periconceptional month of exposure corresponding to reported smoking in B1 only and 98% of mothers who reported 2 or 3 periconceptional months of exposure corresponding to reported smoking in B1–M1 and B1–M2, respectively. Given potentially harmful effects of passive smoke exposure (Hozyasz and Chelchowska,2004; Yilmaz et al,2009), the highest reported duration for passive and/or active smoke exposure was used. For example, if the mother reported 4 months of passive smoke exposure and 3 months of active smoking, the highest reported duration would be 4 months.…”
Section: Methodsmentioning
confidence: 99%
“…Despite evidence in humans of lower vitamin A concentrations among mothers and infants directly or indirectly exposed to cigarette smoke (Hozyasz and Chelchowska,2004; Chelchowska et al,2006; Yilmaz et al,2009) and inhibition of retinol metabolism by alcohol (Deltour et al,1996; Wang,1999; Crabb et al,2001; Molotkov and Duester,2002; Felix et al,2008), exposures to periconceptional cigarette smoking and alcohol consumption in relation to CDH risk have received little attention. Of the existing studies, inconsistent findings have been reported for smoking exposure with significant effects found for paternal smoking and elevated findings for secondary smoke exposure (Zhang et al,1992), but nonsignificant effects reported for maternal smoking (Felix et al,2008).…”
Section: Introductionmentioning
confidence: 99%
“…This early exposure to constituents of cigarette smoke makes children susceptible to respiratory infections, ear infections, growth retardation, and an increased frequency of hospitalizations due to infections (Ladomenou et al, 2009; Yilmaz et al, 2009a). Moreover, these children have decreased serum antioxidant vitamins (A, C, and E), which can contribute to an oxy-cellular redox imbalance and, consequently, increased lipid peroxidation and protein and DNA damage by free radicals present in cigarette smoke (Yilmaz et al, 2009b). Cigarette smoke exposure during pregnancy is related to reduced birth weight, a higher prevalence of sudden infant death syndrome, and impaired child growth, including decreased body mass, length, and head circumference at 3 months of age (Hegaard et al, 2006; Fenercioglu et al, 2009).…”
Section: Worldwide Tobacco Consumptionmentioning
confidence: 99%
“…Few of the advertisements associated with these samples reported the use of caffeine, and none reported tobacco use. Outcomes in infants of mothers who smoke have been shown to be cardiovascular dysregulation, 35 altered sleep/wake patterns, 36 stunted growth, 37,38 and an increase in respiratory ailments. 38 Caffeine is rapidly transferred into human milk and has been shown to cause irritability and poor sleeping patterns in infants of women who have ingested large amounts.…”
Section: Discussionmentioning
confidence: 99%
“…Outcomes in infants of mothers who smoke have been shown to be cardiovascular dysregulation, 35 altered sleep/wake patterns, 36 stunted growth, 37,38 and an increase in respiratory ailments. 38 Caffeine is rapidly transferred into human milk and has been shown to cause irritability and poor sleeping patterns in infants of women who have ingested large amounts. [39][40][41] We previously showed that families seeking milk on the Internet had children with an identified medical condition (21%), intolerance to formula or their mothers' own milk (20%), or a general feeding difficulty (5%).…”
Section: Discussionmentioning
confidence: 99%